JUS POST BELLUM The missing link of Just War Theory: a theoretical examination of what is justice after the war? - Farhatul Mustamirrah Mahamad Aziz; Mohd Rizal Yaaqub (School of Social, Development and Environmental Studies, Faculty of Social Sciences and Humanities, Universiti Kebangsaan Malaysia, 2016)
This theoretical study emphasizes on the missing link of Just War Theory that is justice after the war, jus post bellum. The argument revolves around the reasons jus post bellum should be given the same degree of attention enjoyed by jus in bello (justice in war) in order to fulfil the purpose of Just War Theory in guiding war to achieve peace and justice. The discussion consists of two parts. The first part examines the reasons why jus post bellum was neglected. The second part examines the developing principles of jus post bellum with the emphasis that presently there is no coherent and complete principles of jus post bellum. Results of the examination indicate that more scholarly works should be done in developing the principles of jus post bellum for the restoration of human rights order after the war thus achieving justice after the war. Research is limited because it depends only on existing scholarly works done on jus post bellum. A better developed principle of jus post bellum is important as a way of stigmatizing conquest, of discouraging foreign policy crusades, and of imposing order on post-war reconstruction. The addition of jus post bellum as a category creates a third condition for a just war thus restricting the occurrence of war.